DIAGNÓSTICO Y CAMBIOS ESPACIALES EN EL PARQUE ARQUEOLOGICO DE OLLANTAYTAMBO - Bolívar Yapura, Wilber (2017)
The present work is carried out from the perspective of the Cultural Heritage Management and based on the disturbances and spatial changes that were identified in the area of the Archaeological Park of Ollantaytambo (PAO), based on the information offered in the literature Site, the process of drawing up the ODP Master Plan for 2005, which is now outdated and unfortunately not implemented, as well as its own experiences, offering a situational diagnosis of human settlements through axes, as a document of integration and methodological adequacy.